Impact of Cyclone on Livelihood Pattern in the South Western Coastal Region of Bangladesh: Pirojpur - Dilara Nasrin; Mahmuda Binte Latif; Shamim Al Mamun; Reyad Hossain Arif; Muliadi Muliadi (Hasanuddin University, 2020)
This research was carried out to assess the impact of cyclone on livelihood pattern in Pirojpur district, Bangladesh during January to June, 2017. The study was both qualitative and quantitative type. The primary data were collected using randomly sampling method (42+42+42=126 respondents) from Tushkhali, Bhitabaria and Pattashi villages of Pirojpur district. The secondary data were collected from different journals, articles, books, official documents, thesis papers and also daily newspapers etc. From the study it was observed that monthly income of middle (4001-8000 tk) and high (8001-above tk) income groups ware decreased by 5% and 0.92% respectively while low income people (1-4000 tk) was increased due to decrease of production after Sidr. On the other hand, expenditure ability of low and middle income groups was decreased. Sidr has created a great impact on human health, livestock, fisheries, food habit, crop production and occupation pattern of the affected people. Respondent’s houses were damaged partially (66.78%), 33.22% completely and cultivated land 28.57 % completely by Sidr in study area. Respondents of the study area said that the production of rice (8%), chili (12%), and vegetables (11%) were reduced due to saline water entrance into the crop field after Sidr. Affected people were migrated (temporary 23.10%, local 25% and internal 26.10%) from Pirojpur to Dhaka (53%), Pirojpur to other places (47%) on the post Sidr due to loss of houses, shelters, cultivated land and lack of job opportunity. Among all factors of temporary migration, water logging was the first reason of migrating people of the study area.